The cowgirl's last rodeo - Bouldin, Tabitha (Love inspired., 2023)
"When Callie Wade's horse goes blind, there's only one man who can save her barrel racing career. Brody Jacobs is the best horse trainer she knows--if he's willing to help. She broke his heart when she left him behind to go after rodeo stardom. This time, will they put their hearts on the line to reach the championship...and a future together?" -- Page [4] cover.